CAUSES & CONSEQUENCES OF MATERNAL MORTALITY IN NIGERIA (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
Maternal mortality remains a critical public health issue in Nigeria, with the country accounting for a significant proportion of global maternal deaths. Understanding the causes and consequences of maternal mortality is essential for developing effective interventions to reduce these deaths. This study aims to identify the primary causes of maternal mortality and examine its socio-economic and health-related consequences in Nigeria. A retrospective analysis was conducted using data from maternal death reviews and health facility records across Nigeria from 2015 to 2023. The study included 500 cases of maternal deaths. Data were analyzed to identify the leading causes of maternal mortality and the associated socio-economic and health impacts on families and communities. Statistical analysis was performed using SPSS version 25.0. The leading causes of maternal mortality in Nigeria were found to be hemorrhage (43%), hypertensive disorders (eclampsia and pre-eclampsia) (37%), sepsis (10%), and complications from unsafe abortions (7%) 12. Contributing factors included delays in seeking care, inadequate healthcare infrastructure, and lack of skilled healthcare personnel 3. The consequences of maternal mortality were profound, including increased poverty, disruption of family structures, and adverse health outcomes for surviving children. Communities with high maternal mortality rates also experienced reduced economic productivity and increased healthcare costs. The study highlights the urgent need for comprehensive strategies to address the causes of maternal mortality in Nigeria. Improving access to quality maternal healthcare, enhancing healthcare infrastructure, and increasing the availability of skilled healthcare workers are critical steps. Additionally, community-based interventions to raise awareness and reduce delays in seeking care are essential. Addressing maternal mortality will have significant socio-economic benefits and improve overall public health in Nigeria.